2022
DOI: 10.1038/s41408-022-00615-7
|View full text |Cite
|
Sign up to set email alerts
|

Azacitidine-induced reconstitution of the bone marrow T cell repertoire is associated with superior survival in AML patients

Abstract: Hypomethylating agents (HMA) like azacitidine are licensed for the treatment of acute myeloid leukemia (AML) patients ineligible for allogeneic hematopoietic stem cell transplantation. Biomarker-driven identification of HMA-responsive patients may facilitate the choice of treatment, especially in the challenging subgroup above 60 years of age. Since HMA possesses immunomodulatory functions that constitute part of their anti-tumor effect, we set out to analyze the bone marrow (BM) immune environment by next-gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…The association between MRD negativity and high BM T cells suggests that high T-cell numbers may contribute to the magnitude of the MRD response (Figure 7), consistent with T-cell reconstitution and effective eradication of leukaemic cells in the allogeneic haematological stem cell transplant setting. 32,33 In accordance with these observations, Oral-AZA appeared to augment the kinetics of T-cell recovery after IC. Nevertheless, in a small subset of patients, despite achieving or exceeding T-cell reconstitution after Oral-AZA treatment, residual AML blasts (MRD+) were still observed and were associated with poor outcomes (Figures 1, 7, and Figure S5).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The association between MRD negativity and high BM T cells suggests that high T-cell numbers may contribute to the magnitude of the MRD response (Figure 7), consistent with T-cell reconstitution and effective eradication of leukaemic cells in the allogeneic haematological stem cell transplant setting. 32,33 In accordance with these observations, Oral-AZA appeared to augment the kinetics of T-cell recovery after IC. Nevertheless, in a small subset of patients, despite achieving or exceeding T-cell reconstitution after Oral-AZA treatment, residual AML blasts (MRD+) were still observed and were associated with poor outcomes (Figures 1, 7, and Figure S5).…”
Section: Discussionsupporting
confidence: 72%
“…Overall, 63% of patients exhibited MRD negativity after IC (Table 1). The association between MRD negativity and high BM T cells suggests that high T‐cell numbers may contribute to the magnitude of the MRD response (Figure 7), consistent with T‐cell reconstitution and effective eradication of leukaemic cells in the allogeneic haematological stem cell transplant setting 32,33 . In accordance with these observations, Oral‐AZA appeared to augment the kinetics of T‐cell recovery after IC.…”
Section: Discussionsupporting
confidence: 63%
“…For instance, increased IFN-γ-producing cells and increased T-cell cytotoxicity following decitabine treatment predicted improved therapeutic responses and survival in clinical patients [ 144 ]. In addition, AML patients with elevated pretreatment T cell diversity and those with an increased T cell receptor beta repertoire richness after azacitidine treatment had longer event-free and overall survival [ 147 ]. These data highlight the importance of TIME in dictating the effects of DNMTi on MDS/AML.…”
Section: Epigenetic Therapy and Time Modulationmentioning
confidence: 99%
“…Our group and others have previously demonstrated that HMAs possess potent immunomodulatory functions which could mediate disease control in patients treated with azacitidine. 5 …”
mentioning
confidence: 99%
“…Our group and others have previously demonstrated that HMAs possess potent immunomodulatory functions which could mediate disease control in patients treated with azacitidine. 5 The study of Liu et al makes an important step towards a better understanding of the molecular mechanism underlying HMA treatment. It could also pave the way for novel therapeutic concepts tackling resistance to these drugs.…”
mentioning
confidence: 99%